Glycosylation of extracellular vesicles: current knowledge, tools and clinical perspectives. Issue 1 (1st December 2018) - Williams, Charles; Royo, Felix; Aizpurua-Olaizola, Oier; Pazos, Raquel; Boons, Geert-Jan; Reichardt, Niels-Christian; Falcon-Perez, Juan M.
ABSTRACT: It is now acknowledged that extracellular vesicles (EVs) are important effectors in a vast number of biological processes through intercellular transfer of biomolecules. Increasing research efforts in the EV field have yielded an appreciation for the potential role of glycans in EV function. Indeed, recent reports show that the presence of glycoconjugates is involved in EV biogenesis, in cellular recognition and in the efficient uptake of EVs by recipient cells. It is clear that a full understanding of EV biology will require researchers to focus also on EV glycosylation through glycomics approaches. This review outlines the major glycomics techniques that have been applied to EVs in the context of the recent findings. Beyond understanding the mechanisms by which EVs mediate their physiological functions, glycosylation also provides opportunities by which to engineer EVs for therapeutic and diagnostic purposes. Studies characterising the glycan composition of EVs have highlighted glycome changes in various disease states, thus indicating potential for EV glycans as diagnostic markers. Meanwhile, glycans have been targeted as molecular handles for affinity-based isolation in both research and clinical contexts. An overview of current strategies to exploit EV glycosylation and a discussion of the implications of recent findings for the burgeoning EV industry follows the below review of glycomics and its application to EV biology.